2000
DOI: 10.1037/0022-006x.68.5.923
|View full text |Cite
|
Sign up to set email alerts
|

Drug use and validity of substance use self-reports in veterans seeking help for posttraumatic stress disorder.

Abstract: The present study assessed drug use and the validity of self-reports of substance use among help-seeking veterans referred to a specialty clinic for the assessment of posttraumatic stress disorder (PTSD). Patients (n = 341) were asked to provide a urine sample for use in drug screening as part of an evaluation of PTSD. Self-reports of substance use were compared with same-day supervised urine samples for 317 patients who volunteered to participate in a drug screening. Results suggested that self-reports were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 32 publications
0
41
1
Order By: Relevance
“…Two studies examining self-reported substance use among patients with PTSD found participants' responses to be highly valid, with less than 10% of participants not reporting substance use detected by urine screens. 39,40 Second, although the effects observed remained after controlling for between-group differences in exposure to usual treatment and in the prevalence of childhood sexual abuse and childhood trauma, the outcomes observed may have been influenced by confounding factors not measured by the present study. It could also be argued that the differences observed may be attributed to more general therapist effects (ie, the treatment group received up to 13 sessions with a therapist that the control group did not).…”
Section: Commentcontrasting
confidence: 58%
“…Two studies examining self-reported substance use among patients with PTSD found participants' responses to be highly valid, with less than 10% of participants not reporting substance use detected by urine screens. 39,40 Second, although the effects observed remained after controlling for between-group differences in exposure to usual treatment and in the prevalence of childhood sexual abuse and childhood trauma, the outcomes observed may have been influenced by confounding factors not measured by the present study. It could also be argued that the differences observed may be attributed to more general therapist effects (ie, the treatment group received up to 13 sessions with a therapist that the control group did not).…”
Section: Commentcontrasting
confidence: 58%
“…Objective measures of symptom severity may be particularly useful in PTSD populations where the validity of self-report is often questioned due to issues associated with secondary gain (Calhoun et al, 2000) and negative cognitive biases (Buckley et al, 2000). Further, assessing patients in their home environment avoids the effects of reactivity to the laboratory environment.…”
Section: Discussionmentioning
confidence: 99%
“…Although clinical studies have not yet investigated interactions between these two stress systems, recent findings indicate that administration of the synthetic cannabinoid nabilone to PTSD patients resulted in a highly comparable reduction of treatment-resistant daytime flashbacks and nightmares (56). Moreover, PTSD is often associated with high levels of cannabis consumption (57), which might be related, in part, to an inadequate activation of the endogenous GC and endocannabinoid systems in these patients (58). Furthermore, based on our finding that systemic CORT administration impaired the retrieval of hippocampus-dependent contextual fear memory without affecting the retrieval of hippocampus-independent auditory fear memory, it would seem important to also investigate whether GC or cannabinoid administration might selectively reduce the retrieval of hippocampus-dependent traumatic memories in PTSD patients.…”
Section: Discussionmentioning
confidence: 99%